Morphological Characterization and Identification of Coffea liberica Callus of Somatic Embryogenesis Propagation. - Fitria Ardiyani (Indonesian Coffee and Cocoa Research Institute, 2015)
Compared with other types of coffee, Liberica coffee is more difficult to be propagates using clonal methods. Meanwhile, demand for planting materials and consumption of this type of coffee is increasing lately. The objective of this paper is to present results of the work on morpological characterization of Liberica coffee (Coffea liberica) callus produced by somatic embryogenesis propagation. This research used C. liberica Arruminensis clone. This clone was one of Liberica coffee clones which had superior taste. Main activitis carried out in this experiment were explant sterilization, explant induction and histological analysis on the callus produced. The result of this research showed that non embryogenic callus was higher (72%) than embryogenic callus (28%). The callus description can be used to identify type and characteristic of the callus. Therefore, it can be a parameter to choose type of callus for propagation material. This is important because choosing the right callus is determine of the succesfully process of Liberica somatic embryogenesis. Keywords: somatic embryogenesis, Liberica, embryogenic, non-embryogenic